Cr(VI) and lindane removal by Streptomyces M7 is improved by maize root exudates - Simón Solá, María Zoleica (2017)
Environmental mixed pollution by both organic and inorganic compounds are detected worldwide. Phytoremediation techniques have been proposed as ecofriendly methods for cleaning up polluted sites. Several studies have demonstrated enhanced dissipation of contaminants at the root-soil interface through an increase in microbial activity caused by the release of plant root exudates (REs). The aim of this study was to evaluate the effectiveness for Cr(VI) and lindane removal by Streptomyces M7 cultured in a co-contaminated system in presence of maize REs. Our results showed when REs were added to the contaminated minimal medium (MM) as the only carbon source, microbial removal of Cr(VI) and lindane increased significantly in comparison to contaminant removal obtained in MM with glucose 1 g L−1. The maximum removal of 91% of lindane and 49.5% of Cr(VI) were obtained in the co-contaminated system. Moreover, Streptomyces M7 showed plant growth promoting traits which could improve plant performance in contaminated soils. The results presented in this study provide evidence that maize REs improved growth of Streptomyces M7 when REs were used as a carbon source in comparison to glucose. Consequently, lindane and Cr(VI) removal was considerably enhanced making evident the phytoremediation potential of the actinobacteria-plant partnership.